Notes on the genera Peritropisca Carvalho & Lorenzato and Rewafulvius Carvalho (Hemiptera: Heteroptera: Miridae: Cylapinae), with the description of a new species of Peritropisca from Indonesia - Wolski, Andrzej; Gorczyca, Jacek (Zootaxa, 2013)
The genera Peritropisca Carvalho & Lorenzato, 1978 and Rewafulvius Carvalho, 1972 are redescribed. A description of a new species of the genus Peritropisca from Indonesia—P. laticostata sp. nov. and a redescription of P. bituberculata Carvalho & Lorenzato, 1978 are provided. The genus Euchilofulviella Gorczyca, 1999 is proposed as a junior synonym of Rewafulvius Carvalho, 1972 syn. nov. A color habitus picture of the adult and male genitalia drawings of each treated species are provided. A key to the genus Peritropisca is given.